2022
DOI: 10.3389/fnagi.2022.973054
|View full text |Cite
|
Sign up to set email alerts
|

Potential of brain age in identifying early cognitive impairment in subcortical small-vessel disease patients

Abstract: BackgroundReliable and individualized biomarkers are crucial for identifying early cognitive impairment in subcortical small-vessel disease (SSVD) patients. Personalized brain age prediction can effectively reflect cognitive impairment. Thus, the present study aimed to investigate the association of brain age with cognitive function in SSVD patients and assess the potential value of brain age in clinical assessment of SSVD.Materials and methodsA prediction model for brain age using the relevance vector regress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 44 publications
1
7
0
Order By: Relevance
“…The TMT is used to evaluate visual attention, psychomotor speed, and executive function. Shi et al reported that patients with SVD showed executive dysfunction, which was determined using the TMT score (Shi et al, 2022). Processing speed has been associated with BPS in patients with CAA and likewise, our study revealed that the time taken to complete TMT set-A was longer in patients with BPS.…”
Section: Discussionsupporting
confidence: 70%
“…The TMT is used to evaluate visual attention, psychomotor speed, and executive function. Shi et al reported that patients with SVD showed executive dysfunction, which was determined using the TMT score (Shi et al, 2022). Processing speed has been associated with BPS in patients with CAA and likewise, our study revealed that the time taken to complete TMT set-A was longer in patients with BPS.…”
Section: Discussionsupporting
confidence: 70%
“…As previously described, the raw test scores of each scale were standardized through Z -transformation using the mean and standard deviation for subsequent analysis. Information processing speed scores were calculated based on the composite TMT-A, Stroop-A, and Stroop-B scale scores using the Z -transformed averages.…”
Section: Methodsmentioning
confidence: 99%
“…Further details are provided in the Supporting Information and our previous studies. 27,37,38 Statistical Analyses. Statistical analyses were carried out using SPSS version 22.0 (SPSS Inc. Chicago, Illinois) and R software (version 4.2.1).…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…(5) The extent to which each subject deviates from healthy brain-aging trajectories, expressed as the difference between predicted and chronological age (the brain-predicted age difference, brain-PAD), has been proposed as an index of structural brain health, sensitive to pathology in a wide spectrum of neurological and psychiatric disorders. (6) As a relevant example, brain-age predictions are sensitive to white matter hyperintensities (WMH) and brain volumes, imaging features that are both manifestations of cerebral small vessel disease, (7)(8)(9) which is thought to be the main pathogenetic mechanisms through which FD impacts brain health.…”
Section: Introductionmentioning
confidence: 99%